Practicality of Learning Devices Based on Conceptual Change Model to Improve Concept Mastery of Students in the Gas Kinetic Theory Material - Susilawati, Susilawati; Kusumayati, Baiq Arum; Sutrio, Sutrio; Doyan, Aris (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
This study aims to determine the practicality of learning devices based on conceptual change model to improve concept mastery of students in the gas kinetic theory material. The device was developed with a 4D model consisting of define, design, develop, and disseminate. The learning tools developed are in the form of syllabus, lesson plan, student worksheet, and concept mastery instrument. The data collection was carried out through the distribution of student response questionnaires and observation sheets on the implementation of learning in the eleventh grade MIPA SMAN 1 Kediri. The questionnaire score used consisted of 4 scales, namely a scale of 4 (very good), a scale of 3 (good), a scale of 2 (less), and a scale of 1 (very less). The results showed that the response of students and the implementation of learning were very practical. Based on these data, it can be concluded that the learning device conceptual change model practically to improve concept mastery of students in the gas kinetic theory material